Risk factor-based optimal endoscopic surveillance intervals after endoscopic submucosal dissection for gastric adenoma - Choong-Kyun Noh (Nature Portfolio, 2021)
Abstract To date, there exists no established endoscopic surveillance interval strategy after endoscopic submucosal dissection (ESD) for gastric adenoma. In this study, we suggest a risk factor-based statistical model for optimal surveillance intervals for gastric adenoma after ESD with curative resection. A cox proportional hazard model was applied to identify risk factors for recurrence after ESD. Patients (n = 698) were categorized into groups based on the identified risk factors. The cumulative density of recurrence over time was computed using a cubic splined baseline hazard function, and the customized surveillance interval was modeled for each risk group. The overall cumulative incidence of recurrence was 7.3% (n = 51). Risk factors associated with recurrence were male (hazard ratio [HR], 2.60, P = 0.030), protruded scar (HR, 3.18, P < 0.001), and age ≥ 59 years (HR, 1.05, P < 0.001). The surveillance interval for each group was developed by using the recurrence limit for the generated risk groups. According to the developed schedule, high-risk patients would have a maximum of seven surveillance visits for 5 years, whereas low-risk patients would have biennial surveillance for cancer screening. We proposed a simple and promising strategy for determining a better endoscopic surveillance interval by parameterizing diverse and group-specific recurrence risk factors into a well-known survival model.